Alemtuzumab (CAMPATH 1H) induction therapy in cadaveric kidney transplantation--efficacy and safety at five years. - Watson, C; Bradley, J; Friend, P; Firth, J; Taylor, C; Bradley, JR; Smith, K; Thiru, S; Jamieson, N; Hale, G; Waldmann, H; Calne, R (2005)
Alemtuzumab is a powerful lymphocyte depleting antibody currently being evaluated in solid organ transplantation. This paper describes 5-year results of a single center study of alemtuzumab as induction in renal transplantation. Thirty-three renal transplant recipients received 20 mg alemtuzumab on day 0 and 1, followed by half-dose cyclosporin monotherapy (trough concentration 75-125 ng/mL) from day 3. They were compared in a retrospective contemporaneous-controlled manner with 66 kidney transplant recipients transplanted in the same period and center who received conventional immunosuppression with cyclosporin, azathioprine and prednisolone. In the alemtuzumab group 12% of recipients died compared to 17% in the control group (p = 0.48); likewise graft loss was similar in both groups (21% vs. 26%, respectively, p = 0.58). Incidence of acute rejection was also comparable at 5 years (31.5% vs. 33.6%), although the pattern of rejection was different with 14% patients in the alemtuzumab group experiencing rejection over 1 year post-transplant compared to none in the control group. There was no significant difference between groups in terms of infection or serious adverse events. While acknowledging the limitations of a relatively small single-center study, results suggest that alemtuzumab induction allowed satisfactory long-term patient and graft survival equivalent to that seen with standard triple immunosuppression, while avoiding steroid therapy.